Technology Entrepreneurship Project (ENT 600) : Dick’s Sporting Good / Mohammad Haikal Mohd Jalil - Mohd Jalil, Mohammad Haikal (2021)
This case study in an attempt us to understand the concepts that can be applied to practical situation. As a student at UiTM Arau Perlis, undergoing a case study project is part of a study for all. So for this purpose, I got opportunity to research a company an American sporting goods retail company which is Dick’s Sporting Goods that offering a broad assortment of high quality, competitively-priced brand name sporting goods equipment, apparel and footwear, in a specialty store environment and through its online store. I was able to search and collect about the general company information in the first part of this project report, such as company’s background, technology used and the various types of furniture produces by the company. The objective of the projects id to figure the background, organizational structure, products and service that Dick’s Sporting Good provide. Then, in this case study will contains the specialized subject studies which is I will do a research based on one type of Dick’s sporting good retail product which is canopy. In this case study, I have analysed the SWOT analysis that I can distinguish the strength, weakness , opportunities and threats of this company to find a better technology system solution that can be implemented in this company the deal with the current problems that the company is opposed to. Company needs to progress and develop new strategy and planning for improvement of the existing system are crucial for growth in business development so that the company is not outdated. In this case study I will be explain about my new strategy and planning one of the company retail product which is canopy. Based on my attention to this product I have find some problem that the product are inconvenient with their users. All users that are used canopy will difficult to transport it anywhere such as outdoor recreation, being a medic for competition or even small outlets. The problem is especially problematic for those who only have a sedan car and do not have an MPV car or van. Next, the canopy is not so strong that it allows it to collapse when heavy rain and strong winds hit. Lastly, the material on the roof is not durable, when it is under the sun and rain it will start to rot. In this case study, I will explaining deeper regarding the problems on canopy and I will discussing the alternatives solution towards the problems.